Renovation readiness matrix for cities (Nexo Revista Científica, 2021)
The accumulated positive experience of the housing stock renovation in Moscow puts issues of its distribution in other cities on a current agenda in many regions. The housing stock renovation program has an integrated impact on the social and economic development of the urban environment. However, economic factors are primarily important to the program implementation. The authors of this article have identified a number of economic criteria / parameters that help to assess the readiness for renovation in a particular city. The article introduces a Renovation Readiness Matrix that allows consolidating these parameters.